Respuesta :

Answer:

Step-by-step explanation:

there are two ways to solve systems of equations,  elimination or substitution, this looks like elimination would work quickly

x= 25 -y

x + y = 25   (eq 1)

5x + y = 10  (eq 2)

subtract 2 from 1

x + y = 25  

-(5x + y = 10)

-4x + 0y = 15

-4x = 15

x = - 15/4

now plug in x into either starting equations and solve for y

-15/4 + y = 25

y = 25 + 15/4

y = 100/4 + 15 /4

y = 115 /4

y = 28 3/4

we have solved it :)

Answer:

5x+ y = 10   ---(eq1)

x = 25 - y    ---(eq2)

substituting (eq2) in (eq1)

5(25 - y) + y = 10

125 - 5y + y = 10

125 - 4y = 10

-4y = 10 - 125

-4y = -115

4y = 115

y = 115/4 = 28.75

substituting value of y in (eq2)

x = 25 - 28.75

x = -3.75